Education and power relations. - Méndez, Mario (Teoría y Praxis, 2023)
There is a close relationship between education, social change and the interests of the ruling classes. This link is analysed here on the basis of some fundamental intuitions of Michel Foucault concerning the power relations that create discourses and produce subjects.